Edukasi kesehatan dan pendampingan penggunaan fluoride untuk pencegahan karies gigi pada anak di Desa Lam Cot, Lueng Bata - Mardiah, Ainun; Rahayu, Eka Sri; Febriani, Henny; Reca, Reca; Nuraskin, Cut Aja; Wirza, Wirza; Salfiyadi, Teuku; Mutia, Hera; Nurhaida, Nurhaida (Politeknik Kesehatan Kemenkes Aceh, 2025)
Dental caries is one of the most common health problems among children, closely related to oral hygiene and the use of fluoride. This community service program aimed to improve the knowledge and awareness of parents and children about the importance of fluoride in preventing dental caries. The activity took place in Lam Cot Village, Lueng Bata Subdistrict, Banda Aceh, using methods such as educational lectures, demonstrations of proper toothbrushing techniques, and one-week direct mentoring. A total of 30 elementary school children and 20 parents participated in this program. Evaluation results showed an increase in participants' average knowledge scores from 63.33 to 83.33 (a 20-point improvement) after the implementation of education and mentoring. Additionally, there was an improvement in the compliance of brushing teeth twice a day using fluoride toothpaste. This program had a positive impact on preventing dental caries in children through educational and mentoring approaches.